2006
DOI: 10.1002/pd.1362
|View full text |Cite
|
Sign up to set email alerts
|

Mid-facial anthropometry in second-trimester fetuses with trisomy 21: a three-dimensional ultrasound study

Abstract: The nasal bones are present in the majority of fetuses with trisomy 21 in the second trimester. This group of fetuses has a characteristic mid-facial anthropometry (wider maxillary angle) that can be assessed by means of 3D ultrasonography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…It is mandatory to adhere to standardized measurement techniques when using markers for the estimation of Down syndrome risk in order to prevent overestimation or underestimation of the calculated risk. Several measurement techniques for NBL have been described in the literature (Table S1 online)3, 8, 10–12. 2D ultrasound may lead to overestimation of the NBL if this is measured slightly obliquely and/or the measurement erroneously includes part of the frontal bone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is mandatory to adhere to standardized measurement techniques when using markers for the estimation of Down syndrome risk in order to prevent overestimation or underestimation of the calculated risk. Several measurement techniques for NBL have been described in the literature (Table S1 online)3, 8, 10–12. 2D ultrasound may lead to overestimation of the NBL if this is measured slightly obliquely and/or the measurement erroneously includes part of the frontal bone.…”
Section: Discussionmentioning
confidence: 99%
“…This has raised the question of whether the first published reference ranges, based on 2D images, are still valid and how they compare with the new ones obtained by 3D techniques. Reports on the role of 3D ultrasound in obtaining accurate NBL, PT and FMF angle measurements and individual reference ranges for these markers in the second trimester of pregnancy are available7–10; however, no study has thus far measured all three markers in the same fetus and extended the normal ranges to the third trimester. Although screening programs for trisomies are offered earlier in pregnancy, late diagnosis of chromosomal anomalies is not uncommon, especially in countries with a low uptake of screening programs.…”
Section: Introductionmentioning
confidence: 99%
“…The flat face characteristic of Down syndrome is a consequence of underdevelopment of the maxilla, which has been described in affected fetuses during both the first and second trimesters of pregnancy. [4][5][6][7] Borenstein M. was the first to use ultrasound for prenatal measurement of the frontomaxillary facial (FMF) angle and he reported that it was likely to be a useful adjunct in the screening for trisomy 21 at 11-13 +6 weeks gestation. 8,9 When incorporating the FMF angle into fetal screening for chromosome abnormalities, ethnic differences in the facial profile should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Although usually easily suspected with conventional 2D ultrasound, 3D ultrasound has the potential to visualize several structures in the same image, thus improving the comprehension of spatial relationship and recognition of abnormal features. Abnormalities that can be most reliably diagnosed by 3D ultrasound include distinctive facies such as micrognathia as part of the spectrum of genetic disorders (Figure 3), tumors such as cervical teratomas extending to the face (Figure 4), facial clefts and markers of trisomy 21 (Lee et al , 2003a; Bergann et al , 2006). Diagnosis of abnormalities of the hard and soft secondary palate is amenable to prenatal diagnosis by means of 3D ultrasound (Benacerraf et al , 2006; Faure et al , 2007a).…”
Section: Specific Applications Of 3d Ultrasoundmentioning
confidence: 99%
“…The current literature is extensive and filled with articles addressing the application of 3D ultrasound to virtually every aspect of fetal imaging (Goncalves et al , 2005). The advantages of 3D outlined here include the enhanced identification of the nature, size and location of certain fetal defects (Merz et al , 1995a,b; Platt et al , 1998; Baba et al , 1999; Dyson et al , 2000; Xu et al , 2002); the precise measurement of the volumes of organs with irregular shapes (Kalache et al , 2003b; Ruano et al , 2005); visualizing structures in reconstructed planes (Kalache et al , 2006a,b); imaging of the fetal skeleton (Benoit, 2003); spatial presentation of blood flow arborization and vessels (Chaoui and Kalache, 2001; Kalache et al , 2003a; Lee et al , 2003b); the ability to reconstruct a 3D rendered image of the fetal heart that contains depth and volume which may provide additional information that is not available from two‐dimensional (2D) ultrasound images (DeVore et al , 2003); the storage and retrospective analysis (Lee et al , 2003a; Bergann et al , 2006) and exchange of data that can be used for second opinions (Nelson et al , 2001; Vinals et al , 2005); and the facilitation of maternal–fetal bonding (Ji et al , 2005). Moreover, a study on the perception of non‐pregnant sonographers, sonologists and undergraduate students on the use of 3D ultrasound technology in fetal medicine showed that both caregiver and laypersons believe that 3D ultrasound will play a role in the future, for medical indications and in reassuring patients who are carrying normal fetuses (Lee et al , 2007).…”
Section: Introductionmentioning
confidence: 99%